Influence of doubly-hydrogenated oxygen vacancy on the TID effect of MOS devices - Lu, Guangbao; Liu, Jun; Zheng, Qirong; Li, Yonggang (Frontiers in Materials, 2022)
The total ionizing dose (TID) effect is one of the main causes for the performance degradation/failure of semiconductor devices under high-energy γ-ray irradiation. In special, the concentration of doubly-hydrogenated oxygen vacancy (a case study of VoγH2) in the oxide layer seriously exacerbates the TID effect. Therefore, we developed a dynamic model of mobile particles and fixed defects by solving the rate equations and Poisson’s equation simultaneously, to reveal the contribution and influence mechanisms of VoγH2 on the TID effect of MOS devices. We found that VoγH2 can directly and indirectly promotes the formation of Voγ+ and VoγH+ , respectively, which can increase the electric field near the Si/SiO2 interface and reduce the threshold voltage of silicon MOS devices accordingly. Controlling VoγH2 with the concentration below 1014 cm-3 can suppress the adverse TID effects. The results are much helpful for analyzing the microscopic mechanisms of the TID effect and designing new MOS devices with high radiation-hardening.